Amenaza de aborto en pacientes atendidas en el Departamento de Gineco-Obstetricia del Hospital General Isidro Ayora de Loja en el periodo agosto-octubre del 2015. - Sucunuta Moreno, Katy Soledad (2016)
The menace of abortion is defined as transvaginal indented- TVB before 20 weeks without cervical changes causing the risk of losing your product. Therefore this research work is based on determining the incidence of menace abortion in patients from the department of gynecology and obstetrics in the General Hospital Isidro Ayora of Loja in the period August-October 2015, point out the risk factors that predispose pregnant women to present it, and determine the number of patients who continued with the pregnancy or ended in abortion by gestational age. It is a descriptive, retrospective study, conformed by 1192 medical records, whose sample was 89, same that meet the inclusion criteria where the data collector instrument previously developed by the author was used. Finding the highest incidence in pregnant women from 15 to 19 years with a 34.83%, which was the main trigger urinary and cervicovaginal infections (bacterial vaginosis, vaginal candidiasis) with 40.44% and 33.78% respectively. In 87.64% had a successful progression of pregnancy between weeks 16 to 20 of gestation, while 12,35% ended with abortion in week 7 to 10. The threat of abortion is an obstetric emergency occurs in patients of childbearing age associated with uro-genital infections, which after the application of timely treatment the mother continue her pregnancy. Keywords: menace of abortion and incidence.